2017
DOI: 10.1097/mib.0000000000001201
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Future Nonadherence in Inflammatory Bowel Disease

Abstract: Lower age at diagnosis, flares, feelings of anxiety or depression, and nonadherence are associated with future nonadherence in patients with IBD. Altering illness perceptions could be an approach to improve adherence behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 57 publications
(36 reference statements)
0
24
0
4
Order By: Relevance
“…However, the decision to stop treatment in patients in remission or in patients with mild side effects is more difficult and is influenced by factors such as doctor and patient preference, treatment duration, treatment adherence and costs. It is known that adherence to long-term treatment is generally low, which is associated with suboptimal treatment outcomes and this also might be a reason to stop treatment [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, the decision to stop treatment in patients in remission or in patients with mild side effects is more difficult and is influenced by factors such as doctor and patient preference, treatment duration, treatment adherence and costs. It is known that adherence to long-term treatment is generally low, which is associated with suboptimal treatment outcomes and this also might be a reason to stop treatment [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Rectal use of 5-aminosalicylic acid (5-ASA) along with the use of corticosteroids were reported to be positive predictors of persistence to treatment at 3 months, while the use of corticosteroids at 12 months was no longer a positive predictor. In a multicenter, prospective cohort study including 1,558 patients with CD and 1,054 patients with UC, younger age at diagnosis, flares, feelings of anxiety or depression, and nonadherence were associated with future nonadherence to treatment [13]. A recent study from Bager et al [2] reported young age and smoking as predictors of nonadherence, while high adherence rates were explained by high patient satisfaction and high degree of shared decision making.…”
Section: Introductionmentioning
confidence: 99%
“…This might suggest the lack of understanding of the disease in patients with a low education level, even though a professional gastroenterologist provided adequate comprehensive guidance. A previous study conducted by Severs et al also showed that altering the perception of an illness could be an approach to improve adherence behavior [17]. To some extent, other factors, such as an uninsured status, a low income, and anxiety related to the side effects of the medicine, also played a role in adherence to the guidelines.…”
Section: Discussionmentioning
confidence: 95%